ERP Mediation in Digital Competence, Information Quality, System Automation, and Managerial Decision-Making in Banking - Nurfadila Nurfadila; Moh Zulkifli Murfat; Hartati Hartati; Mahathir Moahamda (Yayasan Vifada Cendikia Indonesia, 2026)
Digital transformation in the banking sector requires more accurate information integration and effective managerial decision-making. This study examines the effects of digital competence, financial information quality, and system automation on managerial decision-making effectiveness, with Enterprise Resource Planning (ERP) utilization serving as a mediating variable. A quantitative survey was conducted involving 100 ERP users from four major banks in Makassar, Indonesia. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). The findings indicate that digital competence, financial information quality, and system automation significantly influence ERP utilization, with digital competence emerging as the strongest predictor. ERP utilization also exerts a substantial positive effect on managerial decision-making effectiveness. Furthermore, ERP utilization mediates the relationships between the three antecedent variables and managerial decision-making effectiveness. These findings contribute empirical evidence to the literature on digital transformation in banking and offer practical implications for strengthening employees’ digital competence, improving financial information quality, and optimizing ERP utilization within banking institutions